Geopolitics of Technology: Technological Competition in Modern Global Politics - Fitri Arianti (Synergisia, 2026)
Technological competition has emerged as one of the most critical dimensions of contemporary global politics. This article examines how technological advancements, particularly artificial intelligence, semiconductors, digital platforms, and green energy technologies have reshaped geopolitical dynamics among the world's major powers. Through a systematic literature review of twenty cutting-edge academic publications, this study identifies four primary arenas of technological competition: (1) digital platform hegemony and data sovereignty; (2) semiconductor supply chains and export controls; (3) green energy transition and critical mineral dependencies; and (4) technological sovereignty and national industrial policy. The findings reveal that US-China technological rivalry has entered a "Tech Cold War" phase with far-reaching implications for the international trading system, global innovation ecosystems, and digital governance frameworks. The implications for developing countries, including Indonesia, are significant, given mounting pressure to choose technological alignments in an increasingly polarized geopolitical landscape.